2020
DOI: 10.1007/978-3-658-28128-1_8
|View full text |Cite
|
Sign up to set email alerts
|

‘We Learn Together’—Translanguaging within a Holistic Approach towards Multilingualism in Education

Abstract: Within two multilingual education projects in the north of the Netherlands a holistic model for multilingualism in education is being tested. This is done through design-based interventions in which in-and pre-service teachers, teacher trainers and researchers co-develop and evaluate multilingual activities for different school types. Results show that through experimenting in a safe environment teachers gradually embraced their pupils' multilingualism. This contradicts earlier findings on teachers strongly fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…Although not always explicitly linked to Ruiz's (1984) orientation of linguistic diversity as a resource, an increased interest in and research on multilingualism in education as a resource has resulted in several models or approaches to promoting learners' multilingualism in the last decades. Some of these approaches have been described as awakening to languages (Candelier et al, 2004), inter-comprehension of related languages (Hufeisen & Marx, 2007), tertiary language didactics (Hufeisen & Neuner, 2004), translanguaging (Duarte et al, 2020;García & Wei, 2014) and approaches that aim at a common language curriculum for all language subjects (Daryai- Hansen et al, 2015). Even though these approaches are different in several respects, Haukås (2016) suggested that they all have some principles in common.…”
Section: Theorymentioning
confidence: 99%
“…Although not always explicitly linked to Ruiz's (1984) orientation of linguistic diversity as a resource, an increased interest in and research on multilingualism in education as a resource has resulted in several models or approaches to promoting learners' multilingualism in the last decades. Some of these approaches have been described as awakening to languages (Candelier et al, 2004), inter-comprehension of related languages (Hufeisen & Marx, 2007), tertiary language didactics (Hufeisen & Neuner, 2004), translanguaging (Duarte et al, 2020;García & Wei, 2014) and approaches that aim at a common language curriculum for all language subjects (Daryai- Hansen et al, 2015). Even though these approaches are different in several respects, Haukås (2016) suggested that they all have some principles in common.…”
Section: Theorymentioning
confidence: 99%
“…Når det står at «hovedformålet med (morsmåls)opplaeringen er å styrke elevenes forutsetninger for å beherske det norske språket» (Utdanningsdirektoratet, 2017, s. 1), er det tydeleg at grunnlaget for å styrka dei minoritetsspråklege sin fleirspråklegheit, fell vekk når dei har opparbeidd seg gode nok ferdigheiter i norsk. Dette vert i forsking omtalt som eit problemorientert syn på fleirspråklegheit (Ruiz, 1984(Ruiz, , 2010Baker, 2011;Hauge, 2014), eller som ei underskotstilnaerming som ser utilstrekkelege språklege eigenskapar på målspråket som grunnen til svake akademiske resultat (Duarte & Günther-van der Meij, 2020;Pulinx et al, 2017;Young, 2014).…”
Section: Teoretiske Perspektivunclassified
“…Det at minoritetseleven ikkje alltid vert møtt på ein likeverdig måte med majoritetseleven i laereplan-og laerebokdiskursen, viser at det ubevisst vert oppretthalde ein ujamn maktrelasjon mellom elevane, og at den norskfaglege praksisen rundt fleirspråklegheit ikkje er blitt ein sjølvfølge. Forsking viser ikkje berre større forskjellar i akademiske prestasjonar mellom majoritetsspråklege og minoritetsspråklege elevar (Duarte & Günther-van der Meij, 2020), men òg at det kjem an på kva språk ein har i repertoaret sitt for om ein snakkar om fleirspråklegheit som ein ressurs eller ikkje (Angelis, 2011;Kjelås & van Ommeren, 2019). Skal laerebokforfattarar og laerarar kunne fungera som endringsagentar, må dei både bevisstgjerast på at einspråklege ideologiar har prega språklaeringsmodellar slik at dei i all hovudsak har vore mynta på einspråklege (Hélot, 2015).…”
Section: Konklusjonunclassified
“…In this context, research highlights the effectiveness of professional development, indicating that teacher's beliefs and practices may transform through their participation in professional development activities, such as receiving theoretical input, observing others, and reflective practices . In addition, there are also examples of multilingual ECEC environments where teachers and children practice translanguaging (Duarte & Günther-van der Meij, 2020;Kirsch & Seele, 2020;Schwartz & Asli, 2014) or engage in multilingual circle activities, e.g., singing, translating and interpreting songs in different languages (Kultti, 2013;Kultti & Pramling, 2021). Kultti (2013) has shown that such activities can provide opportunities for language learning.…”
Section: Ecec Educational Linguisticsmentioning
confidence: 99%